NanoBiotechnology Protocols - Rosenthal, Sandra J.; Wright, David W.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Nanobiotechnology holds the promise of providing revolutionary insight into aspects biology ranging from fundamental questions such as elucidating molecular mechanisms of brain disorders to extraordinary applications such as the detection of a single cancer cell in a population of a million cells.  The second edition of Nanobiotechnology Protocols expands upon the previous editions with current, detailed protocols for nanobiotechnology; imaging and detection. With new chapters that explore nano-bio constructs and toxicology of nanomaterials. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Nanobiotechnology Protocol, Second Edition highlights important current areas of development and directions of the field for the future.
High Aspect Ratio Gold Nanorods: Their Synthesis and Application to Image Cell-Induced Strain Fields in Collagen Films -- Imaging Intracellular Quantum Dots: Fluorescence Microscopy and Transmission Electron Microscopy -- Imaging of Cell Populations in Atherosclerosis Using Quantum Dot Nanocrystals -- Imaging of Endothelial Progenitor Cell Subpopulations in Angiogenesis using Quantum Dot Nanocrystals -- Imaging Single Synaptic Vesicles in Mammalian Central Synapses with Quantum Dots -- Quantum Dot-Based Single-Molecule Microscopy for the Study of Protein Dynamics -- Three-dimensional Molecular Imaging with Photothermal Optical Coherence Tomography -- Detecting Respiratory Syncytial Virus Using Nanoparticle Amplified Immuno-PCR -- Gold Nanoparticle-Oligonucleotide Conjugates for the Profiling of Malignant Melanoma Phenotypes -- Methods for Isolating RNA Sequences Capable of Binding to or Mediating the Formation of Inorganic Materials -- Single-Walled Carbon Nanotube-Mediated Small Interfering RNA Delivery and Silencing Gastrin-Releasing Peptide Receptor in Human Neuroblastoma Cells -- Amino Acid Mediated Linear Assembly of Au Nanomaterials -- Enzyme—Gold Nanoparticle Bioconjugates: Quantification of Particle Stoichiometry and Enzyme Specific Activity -- In Vivo Testing for Gold Nanoparticle Toxicity -- Methods for Studying of Toxicity of Silica-based Nanomaterials to Living Cells.
Keywords: Biotechnology; Nanotechnology; Biotechnology; Nanotechnology